2021
DOI: 10.1016/j.jhep.2020.07.039
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-342-3p is a potent tumour suppressor in hepatocellular carcinoma

Abstract: Financial support statement: This study was supported by the Deutsche Krebshilfe (111147).Data availability: GEO accession numbers for miRNA expression array data (Exiqon) and gene expression profiling data (HZI) are NCBI GEO: GSE152920 and GSE152950. Authors contributions: A.B conceived the idea, designed the study, and provided the conceptual framework for the study. R-M.K, QH, and A.B performed all experiments and analyzed the data. L.vD and J.D helped with the cloning and the in vitro experiments. H-C.T he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 19 publications
2
85
0
1
Order By: Relevance
“…MiRNAs are known to play important roles in the progression of multiple diseases, including liver cancer (17,27). Our research found miR-513a-5p antagomir partially reversed the inhibitory effect of LINC01234 knockdown on liver cancer, further verified the function of miR-513a-5p in liver cancer progression.…”
Section: Discussionsupporting
confidence: 73%
“…MiRNAs are known to play important roles in the progression of multiple diseases, including liver cancer (17,27). Our research found miR-513a-5p antagomir partially reversed the inhibitory effect of LINC01234 knockdown on liver cancer, further verified the function of miR-513a-5p in liver cancer progression.…”
Section: Discussionsupporting
confidence: 73%
“…miRNAs are small endogenous non-coding RNAs, which is able to bind to a variety of specific mRNAs to cause gene silencing. Numerous researchers found that the modulation of miRNAs expression in cancer cells is responsible for activate or inhibit tumorigenesis or metastasis (41). Firstly, miRNAs could directly bind to mRNA to suppress transcription activity of downstream oncogenes or tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…15 For example, miR-342 has been reported to significantly decrease cell proliferation, migration and colony formation in hepatocellular carcinoma. 16 MiR-342 also caused significant inhibition of the proliferation, colony formation, invasion and migration of breast cancer. 17 The DExD RNA helicases contains a conserved core consisting of nine conserved motifs that include the characteristic D-E-x-D motif, which confer ATP hydrolysis and RNA unwinding activities, establishing it as RNA helicase.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have demonstrated that miRNAs usually play carcinogenic or tumor suppressive roles in multiple cancers 15 . For example, miR‐342 has been reported to significantly decrease cell proliferation, migration and colony formation in hepatocellular carcinoma 16 . MiR‐342 also caused significant inhibition of the proliferation, colony formation, invasion and migration of breast cancer 17 …”
Section: Introductionmentioning
confidence: 99%